2021
DOI: 10.3389/fenvs.2021.781646
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Spatial Patterns of Dissolved Oxygen and the Impact Mechanisms in a Cascade River

Abstract: Dissolved oxygen (DO) concentration is an essential indicator for assessment of river ecosystems. A hydrodynamic and water quality mathematical model coupling one-dimensional and two-dimensional models is developed in this study. The characteristics of study area, flow velocity, temperature, and organic contamination are taken as consideration in the scenario setting. The changing processes of DO concentration are simulated in different scenarios, and the effects on DO concentration are discussed. Results indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…The range of DO obtained in this study is consistent with 3.07 -6.53 mg/L reported in Bomadi Creek, Niger Delta Area of Nigeria by Iwegbue et al [55]. The reported DO range for the studied rivers is however; lower than 7.54 -9.25 mg/L obtained in Cascade River in Nanning City, China by Zhong et al [56]. The mean value of DO recorded (3.40±1.15 mg/L) is below the 4.0 mg/L standard by NESREA, [57].…”
Section: Analysis Of Datasupporting
confidence: 90%
“…The range of DO obtained in this study is consistent with 3.07 -6.53 mg/L reported in Bomadi Creek, Niger Delta Area of Nigeria by Iwegbue et al [55]. The reported DO range for the studied rivers is however; lower than 7.54 -9.25 mg/L obtained in Cascade River in Nanning City, China by Zhong et al [56]. The mean value of DO recorded (3.40±1.15 mg/L) is below the 4.0 mg/L standard by NESREA, [57].…”
Section: Analysis Of Datasupporting
confidence: 90%
“…The correlation study showed that TDS, EC, and TH are strongly correlated with each other and are likely influenced by the presence of minerals in the water. The significance of dissolved oxygen (DO) is not only from the perspective of addressing water quality issues (Agnieszka et al, 2014) but also for comprehending the mechanisms and causes that influence its dynamics in water bodies (Hondzo et al, 2013;Zhong et al, 2021). Reduced dissolved oxygen (DO) in rivers has a negative effect on physiological functions, leading to a decline in benthic fauna (Bu et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…concentration in the river. Thus, with the increasing water temperature, the saturated dissolved oxygen decreases, and the re-oxygenation effect in the river decreases accordingly (Zhong et al, 2021).…”
Section: Discussionmentioning
confidence: 98%